2004
DOI: 10.1089/089277904322836767
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Enucleation of the Prostate Combined with Mechanical Morcellation: Two Years of Experience with 196 Patients

Abstract: The HoLEP procedure is an efficacious surgical intervention for symptomatic bladder outlet obstruction with minimal associated morbidity. Wider application and technical refinement will allow the surgeon to reduce the operative time and to render mechanical morcellation safer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 17 publications
4
21
0
1
Order By: Relevance
“…Vavassori et al [19] reported a 6.6% rate of bladder wall injuries during morcellation of prostate tissue. We did not observe morcellator-related bleeding complications in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Vavassori et al [19] reported a 6.6% rate of bladder wall injuries during morcellation of prostate tissue. We did not observe morcellator-related bleeding complications in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported with other lasers. 10,11 The 980 nm diode laser has good coagulative properties and the incidence of bleeding during the procedure was minimal. The patient, in whom haematuria occurred, had bleeding from large vessels at the bladder neck.…”
Section: Discussionmentioning
confidence: 99%
“…A large cohort series of patients who underwent HoLEP (n = 196) was published by Vavassori et al [17] in 2004. Because the functional results were comparable to those of HoLEP-RCTs, bladder mucosa injury was reported in 6.6% patients, transient dysuria in 23%, and UTI in 4.4%.…”
Section: Discussionmentioning
confidence: 99%